2004
DOI: 10.2307/4004024
|View full text |Cite
|
Sign up to set email alerts
|

Can Solid Matrix Priming with GA 3 Break Seed Dormancy in Eastern Gamagrass?

Abstract: Development of methods for breaking seed dormancy in eastern gamagrass (Tripsacum dactyloides, L.) could increase its use. Solid matrix priming, the controlled hydration of seed in a system of solid carrier and water, has been used with some success to enhance germination in warm-season grasses. gibberellic acid (ga3), a known promoter of eastern gamagrass germination, can be added to solid matrix priming systems. In this study, systems were evaluated for conditioning eastern gamagrass seeds using the solid ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…(2) osmotic seed priming was carried out by soaking seeds in a solution of polyethylene glycol (PEG)-6000 with a nominal osmotic potential of 2 1.0 MPa, for which the weight ratios of PEG-6000 and distilled water were calculated with the computer program SPMM (Michel and Radcliffe, 1995); and (3) osmotic priming was also applied in combination with a seed pre-soaking in gibberellic acid (GA 3 ). In agricultural and horticultural species, the latter can further increase benefits associated with priming (Finch-Savage, 1991; Rogis et al, 2004). To this end, we dissolved GA 3 in the PEG solution at a concentration of 1000 mg l 21 .…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) osmotic seed priming was carried out by soaking seeds in a solution of polyethylene glycol (PEG)-6000 with a nominal osmotic potential of 2 1.0 MPa, for which the weight ratios of PEG-6000 and distilled water were calculated with the computer program SPMM (Michel and Radcliffe, 1995); and (3) osmotic priming was also applied in combination with a seed pre-soaking in gibberellic acid (GA 3 ). In agricultural and horticultural species, the latter can further increase benefits associated with priming (Finch-Savage, 1991; Rogis et al, 2004). To this end, we dissolved GA 3 in the PEG solution at a concentration of 1000 mg l 21 .…”
Section: Experimental Designmentioning
confidence: 99%
“…We would thus not generally recommend such a combination, especially as GA 3 , at higher concentrations, can induce development of morphologically abnormal seedlings with reduced fitness (e.g. Rogis et al, 2004). We tested only a limited range of pre-treatments, and variation of factors, such as pre-treatment duration, PEG solution concentration, temperature during the pre-treatment phase or use of other priming methods, may increase pre-treatment efficiency.…”
Section: Wider Implications For Restorationmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experiment, GA 3 showed the best results among all hormonal treatments in all attributes. Previous works revealed that SMP by GA 3 can break seed dormancy and enhance seed germination in eastern gama grass (Tripsacum dactyloides L.) (Rogis et al, 2004). Khan et al (2004) also reported similar trends showing alleviative effect of GA 3 over salt stress on seed germination.…”
Section: Effects Of Smp With Different Elicitorsmentioning
confidence: 62%